Size selectivity of magnetite core- (Ag/Au) shell nanoparticles for multimodal imaging applications - Singh P.; Upadhyay C. (My University, 2025)
The magnetic and optical properties of nanomaterials play a significant role in the selection of the materials to be used for contrast enhancement in different biological and cell imaging techniques. These nanoparticles can also be used as drug delivery agents. The calculation of absorption efficiency and surface plasmon resonance wavelength has been performed using Mie theory and MATLAB programs. The study of spectrum calculated indicates the dependence of several optical properties such as resonance and absorption efficiency peak on ratio of core radius to the thickness of shell. A systematic study on the effect of nanoparticle dimension has been presented which clearly indicates that the optical properties can be modulated across the visible and near infrared range by changing these parameters. These properties of nanomaterials make them suitable for their application as multimodal imaging agents as they are also magnetically active and biocompatible. © 2017 IOP Publishing Ltd.